IMPROVING THE PERFORMANCE EMPLOYEES OF BOGOR REGENCY REGIONAL DEVICE ORGANIZATION THROUGH IMPROVEMENT EMPLOYEE DISCIPLINE, WORK CLIMATE, AND WORK MOTIVATION - Endah Wal Istanawati; Martinus Tukiran; Sufrin Hannan (Journal of Social Studies, Arts and Humanities (JSSAH), 2022)
The purpose of this study is to examine the influence of improving employee discipline, work climate and work motivation on improving the performance of employees of regional device organizations in Bogor Regency. The research population is the executor in the Human Resources Staffing and Development Agency and the Bogor Regency Regional Secretariat as many as 290 people with a sample size of 169 people calculated using the Slovin formula with an error rate of 5%. Data collection for each variable studied using questionnaires with a rating scale. Data analysis techniques use descriptive statistical analysis techniques and inferential statistical analysis techniques. The data analysis in this study used the Partial Least Square Structural Equation Modelling (PLS SEM) method. The results showed: (a) Employee discipline variables have a positive and significant influence on motivational variables. (b) Employee discipline variables have a positive and significant influence on performance variables. (c) Work climate variables have a positive and significant influence on motivational variables. (d) Work climate variables have a positive and insignificant influence on performance variables. (e) Motivational variables have a positive and significant influence on performance variables. (f) The magnitude of the coefficient of parameters for discipline variables on performance through motivation is 0.054 which means there is a positive indirect influence of discipline on performance through motivation. Or it can be interpreted that the higher the value of discipline, the performance through motivation will increase as well. (g) The magnitude of the coefficient of parameters for the working climate variable on performance through motivation is 0.278 which means there is a positive indirect influence of discipline on performance through motivation. Or it can be interpreted that the higher the value of the work climate, the performance through motivation will increase as well.